Social and Personality Development : an Advanced Textbook. - Lamb, Michael E. (Taylor & Francis, 2011)
This new text contains parts of Bornstein€and Lamb's Developmental Science, 6th edition, along with new introductory material, providing a cutting edge and comprehensive overview of social and personality development. Each of the world-renowned contributors masterfully introduces the history and systems, methodologies, and measurement and analytic techniques used to understand the area of human development under review. The relevance of the field is illustrated through engaging applications. Each chapter reflects the current state of knowledge and features an introduction, an overview of.